Productivity and profitability of sweet potato (ipomoea batatas l.), dry bean (Phaseolus Vulgaris) and maize (Zea mays l.) as selected field crops in irrigated smallholder agricultural enterprises (ISAEs) in Vhembe District, Limpopo Province, South Africa - Mavhungu, Tsumbedzo J.; Nesamvuni, Azwihangwisi E.; Tshikolomo, Khathutshelo A.; Mpandeli, Ndivhudzannyi S.; van Niekerk, Johan (Technium Social Sciences Journal, 2022)
The study was conducted as part of assessing the productivity and profitability of irrigated smallholder agricultural enterprises in the Vhembe district. Agro-ecological conditions at Upper Mutale valley (sub-humid) and Madimbo Corridor smallholder irrigation schemes (semi-arid) are significantly different. This confirms that the variables of smallholder irrigation schemes are affected by diversity and similarities attributed to different livelihood needs. The purpose of the study was to assess the influence of productivity and profitability on irrigated smallholder agricultural enterprises in the Vhembe District. A representative sample was based on the number of irrigated smallholder irrigation entrepreneurs per irrigated smallholder irrigation production area within the two identified agro-ecological zones. Primary data were collected using a questionnaire and village walk (observation). At least 294 women and youth smallholder irrigation entrepreneurs were sampled for interviews and prompt responses on the influence of productivity and profitability of selected field crops (Dry bean, Sweet Potatoes and Maize) on irrigated Smallholder Agricultural Enterprise. The study applied both primary and secondary data collection instruments. An average selected mean output of irrigated smallholder agricultural product were determined. The results through comparison between informal and formal markets show that the ISAEs who rely on the informal market is making more profit than the formal market. In selling through the formal market, the market deducts 5% of commission while the market agent deducts 7.5% of sales on the gross value of the sold product. This doesn’t include the transportation charges to the market. The Farm Gate market opportunity seems to be the most predominant approach of marketing at ISAEs. These results re-affirms that ISAEs can also be alternative employment to Women and Youth who remain at home while their counterpart is looking for employment in cities. In the end, the study provides strong motivation on socio-economic impact assessment examines how an irrigated smallholder agricultural area has and will change the lives of current and future residents of a community and its local economy.